Preparation of cheese bread added with whey powder - Tesser, Ionara Casali (2013)
Cheese whey is a byproduct of Dairy industry of great nutritional importance, which can also be used in cheese bread due to its potentiality. So, this study aimed at comparing two formulations of cheese bread: the first one, at 5% solution of cheese whey was added in water (F1) and the other added with some fluid milk and the same solution of 5% of whey (F2). The compositional and microbiological characteristics and sensory quality of cheese bread were evaluated. The results indicated that protein and fat contents for F1 and F2 were similar. Microbiological analyses showed an agreement of all formulations. The sensorial analysis, according to a hedonic scale, evaluated attributes as color, texture, aroma, flavor and the whole quality. There was a significant difference among formulations only for the color attribute. An acceptability evaluation of formulations and market issue were also carried out. There was a good acceptability to formulations and the majority of respondents (90%) showed some knowledge on the use of cheese whey as an ingredient. They also showed up their frequent consume of products that contain cheese whey (76%) and stated that they would consume cheese bread added to whey in its formulation (86%). Thus, from this research, it can be inferred that the use of cheese whey to produce cheese bread, based on tested formulations, showed adequate compositional, microbiological and sensorial answers, as well as the final product has acceptability and market potential, so that the second formulation was the best one according to the studied conditions.